Developing a holistic 'vulnerability-resilience' model for local and regional development. Issue 12 (1st December 2020) - Faulkner, Jon-Paul; Murphy, Enda; Scott, Mark
ABSTRACT: Over the last decade, resilience has emerged as a key concept in spatial planning theory and practice to understand how places should respond to change in an era marked by insecurity, systemic risks and the coupling of economic uncertainty with global environmental risks. However, commentators have noted that resilience requires further conceptual clarity before it can constitute a basis for policy action and to prevent it becoming an elastic or fuzzy concept. In this paper, we seek to contribute to these debates by outlining a holistic vulnerability-resilience model based on four key components – exposure (relating to pre-shock attributes), sensitivity (relating to negative impacts caused by shock), capacity of response (relating to pre-shock attributes) and adaptive capacity (relating to positive responses to shock). As such, exposure and sensitivity relate to interpretations associated with vulnerability, while capacity of response and adaptive capacity relate to prevailing interpretations associated with resilience. This approach moves beyond viewing vulnerability as simply the equal but opposite side of resilience and vice versa. In developing a more holistic approach, we aim to bridge the gap between studies that focus exclusively on either vulnerability 'or' resilience, and which often neglect how these two concepts inter-relate and interact.